Penentuan Pusat Pertumbuhan pada Satuan Wilayah Pengembangan (SWP) Kediri Provinsi Jawa Timur - Danu Hadi Basito; R. Riniati; Sebastiana Viphindrartin (e-Journal Ekonomi Bisnis dan Akuntansi, 2019)
Research conducted aims to: 1) to identify the potential economic sectors as the base sector as a determinant of the central region of growth in the Region Development Unit (RDU) Kediri East Java; 2) to identify economic sectors that have a competitive advantage in the Region Development Unit (RDU) Kediri East Java; (3) to classify the region in each Regency / City in the Region Development Unit (RDU) Kediri East Java; (4) to identify region based on the availability of service facilities in Region Development Unit (RDU) Kediri East Java; and (5) to identify region with potential interaction strength among regions as the central development areas in Region Development Unit Kediri East Java'. An analysis method that used a method of quantitative descriptive analysis by using secondary data obtained from the Statistic Indonesia and other institutions needed. The analysis is use location quotient analysis, shift share analysis, typologi klassen analysis, scalogram analysis, dan gravitation model analysi. The Analysis showed Kediri City emerges as a growth poles in Region Development Unit Kediri East Java with regional advantages from two aspects namely regional capability (Location Quotient analysis) and high per capita income (Tipology Klassen analysis) with hinterland area such as Kab. Nganjuk, Kab. Trenggalek, and Kab. Kediri and Kab. Tulungagung. Keywords: Gravitation, Growth Poles, Location Quotient, Scalogram, Shift Share, Typologi Klassen.